Switching Intention in Halal Cosmetics Products - Yessy Fortunania Sutanto; Auditia Setiobudi; Kezia Novtavia Sugiharto (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
The purpose of this research is to examine the switching intention towards Wardah Cosmetics products using the push-pull-mooring theory. The push factors tested in this study are dissatisfaction with the brand image factor, and the mooring factor is switching cost The technique used in this study is purposive sampling. 120 samples of non-Wardah users were obtained through an online questionnaire. The data analysis method uses multiple linear regression modelling. This study found that there is an influence of push factors and pull factors on switching intention. The mooring factor in this study (switching cost) was found to have no significant effect on switching intention. The results of this study can be used to understand the switching intention in cosmetics products with the help of the push-pull-mooring theory.